Strengthening The Maritime Security System in Realizing Indonesia as The Global Maritime Fulcrum - Muhammad Rafi Darajati (Magister of Law, Faculty of Law, University of Mataram, 2022)
The realization of Indonesia’s vision to become the Global Maritime Fulcrum depends on eradicating illegal fishing, reducing overfishing, and rehabilitating damaged marine and coastal environments. However, there are still frequent violations, and exploration in Indonesian waters has not been maximized, so the desire to realize Indonesia as the Global Maritime Fulcrum will be difficult to achieve. This study intends to examine how to strengthen the maritime security legal system to realize Indonesia as the Global Maritime Fulcrum. The research approach used is normative juridical. The author uses a qualitative approach to secondary legal data. The data is in the form of interviews related to the efforts made by stakeholders towards strengthening the maritime security system and realizing the vision of the Global Maritime Fulcrum. This study indicates that to realize Indonesia as the Global Maritime Fulcrum is to strengthen its maritime security system. There are three indicators based on legal system theory, namely optimal maritime security institutions, especially Indonesia Coast Guard, strengthening legal products related to eradicating illegal fishing, improving maritime security infrastructure, and creating new branding to continue to remind the public that Indonesia is a maritime state.